SPECT (Single photon emission tomography): Gama câmara, reconstrução tomográfica e características funcional - Mattos, Fabio Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The SPECT (Single Photon Emission Computed Tomography) systems are part of a medical image acquisition technology which has been outstanding, because the resultant images are functional images complementary to those that give anatomic information, such as X-Ray CT, presenting a high diagnostic value. These equipments acquire, in a non-invasive way, images from the interior of the human body through tomographic mapping of radioactive material administered to the patient. The SPECT systems are based on the Gamma Camera detection system, and one of them being set on a rotational gantry is enough to obtain the necessary data for a tomographic image. The images obtained from the SPECT system consist in a group of flat images that describe the radioactive distribution on the patient. The trans-axial cuts are obtained from the tomographic reconstruction techniques. There are analytic and iterative methods to obtain the tomographic reconstruction. The analytic methods are based on the Fourier Cut Theorem (FCT), while the iterative methods search for numeric solutions to solve the equations from the projections. Within the analytic methods, the filtered backprojection (FBP) method maybe is the simplest of all the tomographic reconstruction techniques. This paper's goal is to present the operation of the SPECT system, the Gamma Camera detection system, some tomographic reconstruction techniques and the requisites for the implementation of this system in a Nuclear Medicine service

Os sistemas SPECT (Single Photon Emission Computed Tomography) fazem parte de uma tecnologia de aquisição de imagens médicas cuja importância vem ganhando mais destaque, pois as imagens resultantes são imagens funcionais complementares àquelas que trazem informações anatômicas, como tomografia computadorizada por raios X, possuindo um alto valor diagnóstico. Esses equipamentos obtêm, de modo não invasivo, imagens do interior do corpo humano através do mapeamento tomográfico de material radioativo administrado ao paciente. Os sistemas SPECT se baseiam no sistema de detecção de Gama Câmaras, sendo que uma Gama Câmara montada em um gantry rotacional é suficiente para obter os dados necessários para uma imagem tomográfica. As imagens obtidas pelos sistemas SPECT consistem em um conjunto de imagens planas que descrevem a distribuição da radioatividade no paciente. Os cortes tomográficos transaxiais são obtidos a partir de técnicas de reconstrução tomográfica. Existem métodos analíticos e iterativos para realizar a reconstrução tomográfica. Os métodos analíticos baseiam-se no Teorema do Corte de Fourier (TFC), enquanto que os métodos iterativos procuram soluções numéricas para resolver as equações das projeções. Dentre os métodos analíticos, o método da retroprojeção filtrada (filtered backprojection – FBP) talvez seja o mais simples de todas as técnicas de reconstrução tomográfica. Este trabalho tem como objetivo apresentar o funcionamento do sistema SPECT, o mecanismo de detecção Gama Câmara, alguns métodos de Reconstrução tomográfica, e requisitos para implantação deste sistema em um serviço de Medicina Nuclear
Keywords: Medicina nuclear